2006
DOI: 10.1111/j.1447-0756.2006.00463.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete mole coexistent with a twin fetus

Abstract: We report two cases of a complete hydatidiform mole coexistent with a live fetus diagnosed by DNA polymorphism analysis. A 27-year-old woman revealed symptoms of pre-eclampsia and ultrasound showed multicystic tumor and placenta coexistent with a live fetus at 16 weeks' gestation. The placenta with partly hydropic change and the fetus without anomaly were consequently evacuated. Another 30-year-old woman had a multicystic mass attached to a normal placenta with a 20-week live fetus on ultrasound examination. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 25 publications
0
20
0
1
Order By: Relevance
“…[3][4][5][6][7][8] Patients with an isolated CHM have a 15% to 20% risk of pGTD. The available literature addressing pGTD in twin gestations involving a hydatidiform mole and a structurally normal live fetus is conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3][4][5][6][7][8] Patients with an isolated CHM have a 15% to 20% risk of pGTD. The available literature addressing pGTD in twin gestations involving a hydatidiform mole and a structurally normal live fetus is conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…2 Complications associated with a molar pregnancy, such as hypertensive disorders of pregnancy, hyperthyroidism, hemorrhage, pulmonary edema, and thromboembolic phenomena, appear to be increased among CHMs coexistent with a live twin fetus. [3][4][5][6][7][8] Also, there may be a higher risk of persistent gestational trophoblastic disease (pGTD) in these patients than in patients with an isolated CHM pregnancy. [3][4][5][6][7][8] In most reports of complete moles coexistent with a live fetus, the live fetus is structurally and karyotypically normal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There has even been a report of a primary pulmonary choriocarcinoma [11]. Some authors have found the risk of severe preeclampsia to be elevated (25.8%) in CHMTF [12,13], but others have not found any significant differences with respect to singleton complete molar pregnancies [14]. Severe preeclampsia is indicative of poor outcome and is usually correlated with the presence of a theca-lutein cyst [15].…”
Section: Discussionmentioning
confidence: 99%
“…According to some reports, CHMTF carries more risk than a singleton complete mole, with reported rates of 55% [20], 43% [12] and 50% [5,18]. Vaisbuch et al [21] suggested that abnormal trophoblastic tissue was more aggressive in twin pregnancies, but Sebire et al [22], who have published the largest series to date (77 cases), reported a similar risk level to that seen with singleton complete moles (16%).…”
Section: Discussionmentioning
confidence: 99%